2007
DOI: 10.1016/j.mod.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the mouse protein Ser/Thr phosphatase 2Cβ gene leads to early pre-implantation lethality

Abstract: Protein phosphatase 2Cbeta (PP2Cbeta) is a member of a family of protein Ser/Thr phosphatases (PP2C) that is composed of at least twelve different gene products. Recent studies have revealed that PP2Cbeta mRNA accumulates in mature sperm, unfertilized metaphase II-arrested oocytes and zygotes, but that the mRNA level then decreases sharply between the early two-cell and eight-cell stages, remaining at low levels during the 16-cell to blastocyst stages of mice. These observations raised the possibility that PP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
(59 reference statements)
1
20
0
Order By: Relevance
“…As Ppm1b KO mouse is pre-implantation lethal 31 , we generated a Ppm1b gene-trap mouse line ( Ppm1b +/d ) using embryonic stem cells containing a retroviral gene trap in the second intron of the Ppm1b locus (Fig. 4f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Ppm1b KO mouse is pre-implantation lethal 31 , we generated a Ppm1b gene-trap mouse line ( Ppm1b +/d ) using embryonic stem cells containing a retroviral gene trap in the second intron of the Ppm1b locus (Fig. 4f).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that gene deletion of Ppm1b led to early pre-implantation lethality in mice 31 . Although Rip3 knockout can rescue spontaneous necroptosis in Ppm1b knockdown cells, Rip3 KO cannot rescue the lethality of Ppm1b gene deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Since PPM1A protein levels were suggested to be a key factor for its activation [11,15], we speculate that accumulation of PPM1A has an essential role in regulating post-translation modification processes during oogenesis. Moreover, the fact that PPM1B was found to be elevated during early stages of pre-implantation in embryonic development, and knockout of PPM1B led to embryonic lethality, indicates the important role of the PPM1 family in mouse embryonic development [30]. Though a growing mouse oocyte, arrested at diplotene of the first meiotic prophase, is transcriptionally and translationally active, a large number of synthesized mRNAs are not used for immediate translation but instead are stored to support oocyte maturation and early pre-implantation embryogenesis [31].…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, not clear what the endogenous substrates for PP2Cβ are. In mouse, PP2Cβ has essential functions in early development, as a PPM1B knock-out mouse model shows an early pre-implantation lethality 20. Most likely, redundancy of family members of PPM1B rescues the early lethality in human.…”
Section: Discussionmentioning
confidence: 99%